ECONOMICS OF HEALTHCARE SYSTEMS AND POLICIES IN DEVELOPING COUNTRIES (American Journal of Business Management, Economics and Banking, 2024)
Health economics is poorly developed in the francophone community. There is little published work addressing developing francophone countries, and it is largely limited to the sub-Saharan Africa. Few specialist research workers from developing countries contribute. Universities only propose global analyses, and other groups involved (expert consultants) only conduct narrow studies, targeted at immediate action or decision making. The article analyses some of the reasons from this underdevelopment, and overviews what has been produced over the last 15 years.